SARS-CoV-2 infection increases risk of intracranial hemorrhage - Hawsawi, Zuhair; Khan, Dilaware; Fischer, Igor; Cornelius, Jan Frederick; Hänggi, Daniel; Muhammad, Sajjad (Frontiers in Human Neuroscience, 2022)
Introduction: SARS-CoV-2 virus infection causes a dysbalanced and severe inflammatory response including hypercytokinemia and immunodepression. Systemic inflammation triggered by viral infection can potentially cause vascular damage, which may lead to cardiovascular and neurovascular events. Research Question: The aim was to investigate whether CNS complications are related to COVID-19. Material and Methods: We examined 21 patients suffering from stroke and intracranial hemorrhage (ICH), 9 (43%) of them male. We compared relative frequencies using Fisher’s exact test. As we had few observations and many variables, we used principal component analysis (PCA) to reduce data dimensionality. We trained a linear support vector machine (SVM) on the first two PCs of the laboratory data to predict Covid-19. Results: Patients suffering from stroke or ICH either had hypertension or SARS-CoV-2 infection, but seldom both (OR=0.05, p=0.0075). Presence of SARS-CoV-2 infection was strongly associated with the logarithm of CRP (p = 1.4e-07) and with D-DIMER (p = 1.6e-05) and moderately with PT (p = 0.0024). SARS-CoV-2 infection was not related to any other factor. CRP, D-DIMER, PT and INR were all related to each other (R2 ranging from 0.19 to 0.52, p ranging from 0.012 to < 0.0001). The first two PCs covered 96% of the variance in the four variables. Using them, perfect linear discrimination between patients suffering from Covid-19 and the other patients could be achieved. Discussion and Conclusion: SARS-CoV-2 infection causes systemic inflammation, which is suggested as a predictor of severe course of ICH. SARS-CoV-2 infection is an additional risk factor for vascular complications.